Assessment of Cellular, Developmental, and Neuromuscular Toxicity of Nanochitin-Loaded PEO/PVA Nanocomposite Hydrogels - Kirdar, Sedef; Kumral, Ulas; Dogan, Serap; Diken, Mehmet Emin; Yilmaz Kardas, Begumhan (SAGE PUBLICATIONS LTD, 2025)
Nanoparticles are widely recognized for their ability to cross biological membranes and modulate cellular functions. In this study, we developed and characterized nanocomposite hydrogels composed of nanochitin (NC) embedded within a PEO/PVA polymer matrix. The materials were physicochemically characterized using zetasizer analysis, FTIR-ATR spectroscopy, and SEM imaging. Their cytotoxic potential was assessed in vitro using MTT assays on normal adult human dermal fibroblast (HDFa) cells, while developmental and neuromuscular toxicities were evaluated in vivo using Drosophila melanogaster as a model organism. Our findings indicate that all NC-doped PEO/PVA nanocomposites were non-toxic to HDFa cells. In fact, 1%, 2.5% and 5% NC-doped PEO/PVA samples showed 44.6%, 20.7% and 13.7% increases compared to negative control, respectively (p < 0.05). However, developmental toxicity assays revealed significant reductions in pupariation and survival rates, with the exception of the PEO/PVA/NC (1%) sample, which showed no adverse effects on the eclosion process. Neuromuscular assays, including larval crawling and adult climbing tests, demonstrated that while larval locomotion remained unaffected across all samples, climbing ability was significantly reduced in the 2.5% and 5% NC- biomaterial-doped groups.
Keywords: PEO; PVA; nanochitin; nanocomposite; hydrogel; fibroblast; drosophila melanogaster; DROSOPHILA-MELANOGASTER; NANOPARTICLES; CHITIN; NANOMATERIALS; Biotechnology & Applied Microbiology; Materials Science; Polymer Science